Big N Auditors and Audit Quality: New Evidence from Quasi-Experiments - Jiang, John (Xuefeng); Wang, Isabel Yanyan; Wang, K. Philip (The Accounting Review, 2019)
ABSTRACT Whether Big N auditors provide higher audit quality than non-Big N auditors remains a debate. We add new evidence to this debate by utilizing the setting of Big N auditors' acquisitions of non-Big N auditors. We identify 331 treatment firms that switched to Big N auditors due to the exogenous shocks imposed by Big N acquisitions. Our difference-in-differences analyses show that treatment firms' audit quality improves after switching to Big N auditors. In comparison, mergers or acquisitions among non-Big Ns have little impact on audit quality. Our cross-sectional analyses suggest the audit quality improvement among treatment firms is more likely due to Big N auditors' general competence rather than their industry-specific expertise. Finally, we find that treatment firms experience no significant market reactions around the announcements of Big N acquisitions, indicating that the capital markets may not attach any premium to the improved audit quality associated with Big N auditors. JEL Classifications: M41; M49.